Political Action, Ethics and Morenist Government. Reflections on Social Justice and Democracy in Mexico - Lindor, Moïse; Hernández-Quezada, Víctor-Jesús; Bernal-Palafox, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The objective of this article is to describe the classic political foundations related to the actions and ideologies of the Morenista administration to confront corruption, marginalization, and promote respect for human rights and social justice in Mexico. Likewise, the philosophical and sociological theories of certain contemporary authors are considered to better analyze the political-ideological position of the current president from objectivity. It is a qualitative study of descriptive-documentary type. The conclusion is that President Andrés Manuel coupled with political and religious ontologies that helped him win electoral contests, they influence government actions that seek to transform and strengthen democratic institutions based on goodness, morality, inclusion social and wellness programs.